Pengaruh Promosi di Instagram Terhadap MinatBerkunjung Wisatawan Pada Pantai Lon Malang Sampang - Maisun, Maisun; Suyono, Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research discusses the problem of promotion on Instagram at the Lon Malang Beach Sampang tourist attraction. The purpose of this study was to determine the effect of Lon Malang Beach Promotion on Instagram through 4C (Context, Communications, Collaborations, and Connections) on Tourist Interest. This study uses a quantitative approach using the Multiple Linear Regression Analysis method, with a total of 98 respondents. The results of this study indicate that the Context (X1), Communications (X2), Collaborations (X3), and Connections (X4) variables have a positive and significant effect on tourist interest (Y). Based on the results of the coefficient of determination test, the results show that promotion on Instagram through Context (X1), Communications (X2), Collaborations (X3), and Connections (X4) has an influence on visiting interest (Y) of 80.0% while the remaining 20.0% is influenced by other variables not discussed in this study.